Evaluation of the impact of chemical control on the ecology of Rattus norvegicus of an urban community in Salvador, Brazil. - Arsinoê Cristina Pertile; Ricardo Lustosa; Ticiana Carvalho-Pereira; Gabriel Ghizzi Pedra; Jesus Alonso Panti-May; Udimila Oliveira; Caio Graco Zeppelini; Fábio Neves Souza; Daiana S Oliveira; Hussein Khalil; Mitermayer G Reis; James Childs; et al. (PLoS ONE, 2022)
Background The presence of synanthropic rodents, such as Rattus norvegicus, in urban environments generates high costs of prophylaxis and control, in large part due to the environmental transmission of the pathogenic spirochete Leptospira interrogans, which causes leptospirosis. In Salvador, Brazil, The Center for Control of Zoonosis (CCZ) is responsible for planning and implementing Rodent Control Programs (RCP) which are based on chemical rodenticide. However, these strategies have not been standardized for use in developing countries. Aim This study aimed to identify the effect of a chemical control campaign on the demographic variables of urban R. norvegicus, analyzing relative abundance, sex structure, body mass, and age of the population, as well as the characterization of spatial distribution among households, rodent capture campaigns and interventions. Methods This study was carried out during 2015 in three valleys of an urban poor community in Salvador. Individuals of R. norvegicus were systematically captured before (Pre-intervention) and three months (1st post-intervention) and six months (2nd post-intervention) after a chemical control intervention conducted by the CCZ in two valleys of the study area while the third valley was not included in the intervention campaign and was used as a non-intervention reference. We used analysis of variance to determine if intervention affected demographic variables and chi-square to compare proportions of infested households (Rodent infestation index-PII). Results During the chemical intervention, 939 households were visited. In the pre-intervention campaign, an effort of 310 trap nights resulted in 43 rodents captured, and in the 1st and 2nd, post-intervention campaigns resulted in 47 rodents captured over 312 trap nights and 36 rodents captured over 324 traps-nights, respectively. The rodent infestation index (PII) points did not show a reduction between the period before the intervention and the two periods after the chemical intervention (70%, 72%, and 65%, respectively). Regarding relative abundances, there was no difference between valleys and period before and two periods after chemical intervention (trap success valley 1: 0,18; 0,19; 0,18 / Valley 3 0,15; 0,17; 0,13/ P>0,05). Other demographic results showed that there was no difference in demographic characteristics of the rodent population before and after the intervention, as well as there being no influence of the application of rodenticide on the areas of concentration of capture of rodents between the campaigns. Conclusion Our study indicates that the chemical control was not effective in controlling the population of R. norvegicus and provides evidence of the need for re-evaluation of rodent control practices in urban poor community settings.